2018
DOI: 10.1371/journal.pone.0205905
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor TFIIEβ interacts with two exposed positions in helix 2 of the Antennapedia homeodomain to control homeotic function in Drosophila

Abstract: Homeoproteins contain the conserved homeodomain (HD) and have an important role determining embryo body plan during development. HDs increase their DNA-binding specificity by interacting with additional cofactors outlining a Hox interactome with a multiplicity of protein-protein interactions. In Drosophila, the first link of functional contact with a general transcription factor (GTF) was found between Antennapedia (Antp) and BIP2 (TFIID complex). Hox proteins also interact with other components of Pol II mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…2 that most of these residues are on the outer surface of the homeodomain. Since both of these helices have been proposed to mediate protein-protein interactions in some homeodomains, including those of the PRD class (Wilson et al 1995;Simon et al 1997;Zaffran and Frasch 2005;Plaza et al 2008;Altamirano-Torres et al 2018), we propose that this selection has altered ETCHbox protein-protein binding properties. Madissoon et al (2016) found that homeodomain differences are not sufficient to explain the differing transcriptional effects of PRD-like genes, implying that other protein domains also contribute to specificity; we therefore suggest that sites outside of the homeodomain that are under selection also influence specificity.…”
Section: Discussionmentioning
confidence: 99%
“…2 that most of these residues are on the outer surface of the homeodomain. Since both of these helices have been proposed to mediate protein-protein interactions in some homeodomains, including those of the PRD class (Wilson et al 1995;Simon et al 1997;Zaffran and Frasch 2005;Plaza et al 2008;Altamirano-Torres et al 2018), we propose that this selection has altered ETCHbox protein-protein binding properties. Madissoon et al (2016) found that homeodomain differences are not sufficient to explain the differing transcriptional effects of PRD-like genes, implying that other protein domains also contribute to specificity; we therefore suggest that sites outside of the homeodomain that are under selection also influence specificity.…”
Section: Discussionmentioning
confidence: 99%
“…2 C and F ). In the same way, either the HD deletion of Antp in AntpΔHD or the HD helix 2 mutant Antp I32A−H36A [ 22 ] reduced the formation of the Antp-TBP-TFIIEβ trimer in a highly significant manner ( E = 0.13 ± 0.09 and E = 0.17 ± 0.10 respectively; Fig. 2 D-F).…”
Section: Resultsmentioning
confidence: 86%
“…TBP interacts with CDX1 via the HD but not with CDX2, supporting the selective interaction of TBP with homeoproteins [ 34 ]. Like other homeoproteins, Antp interacts with other members of the basal transcription machinery as BIP2/TAF3, Med19, TFIIEβ and M1BP [ 14 , 19 22 ], denoting the implication of homeoproteins in the Preinitiation Complex (PIC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interaction between the bait and prey reconstitutes a detectable fluorescing molecule (Kerppola, 2008). In flies, BiFC has previously been used to detect interactions between cytoskeletal proteins (Gohl et al, 2010), transcription factors (Hudry et al, 2012;Altamirano-Torres et al, 2018;Bischof et al, 2018), and myofibril proteins (González-Morales et al, 2019b). Here, we present a detailed BiFC protocol to study protein-protein interactions in Drosophila myofibrils.…”
mentioning
confidence: 99%